Modulation of rotavirus severe gastroenteritis by the combination of probiotics and prebiotics - González Ochoa, Guadalupe; Flores Mendoza, Lilian K.; Icedo Garcia, Ramona; Gómez Flores, Ricardo Alberto; Tamez Guerra, Patricia (2017)
Abstract Annual mortality rates due to infectious diarrhea are about 2.2 million; children are the most vulnerable age group to severe gastroenteritis, representing group A rotaviruses as the main cause of disease. One of the main factors of rotavirus pathogenesis is the NSP4 protein, which has been characterized as a viral toxin involved in triggering several cellular responses leading to diarrhea. Furthermore, the rotavirus protein NSP1 has been associated with interferon production inhibition by inducing the degradation of interferon regulatory factors IRF3, IRF5, and IRF7. On the other hand, probiotics such as Bifidobacterium and Lactobacillus species in combination with prebiotics such as inulin, HMO, scGOS, lcFOS have been associated with improved generalized antiviral response and anti-rotavirus effect by the reduction of rotavirus infectivity and viral shedding, decreased expression of NSP4 and increased levels of specific anti-rotavirus IgAs. Moreover, these probiotics and prebiotics have been related to shorter duration and severity of rotavirus diarrhea, to the prevention of infection and reduced incidence of reinfections. In this review we will discuss in detail about the rotavirus pathogenesis and immunity, and how probiotics such as Lactobacillus and Bifidobacterium species in combination with prebiotics have been associated with the prevention or modulation of rotavirus severe gastroenteritis. Keywords Rotavirus · Pathogenesis · Probiotics · Prebiotics